THEMATIC ANALYSIS OF EMILY DICKINSON’S EARLY POETRY - Gaybulloyeva , Vazirabonu Shokirovna; Khamdamova, Sitora Bakhshilloyevna (Educational Research in Universal Sciences, 2024)
Emily Dickinson occupied a very prestigious position in the field of American literature. Her poetry deals with a unique and large number of thematic expressions. This article focuses on the analysis of Emily Dickinson’s poems, the main ideas of her poetry are discussed separately. First of all, in this article, the unique features of the poet’s work are emphasized, and the movements in which the poet wrote are expressed in sequence. Many researchers and critics have spent their great exertion to trace out these themes and they became successful in this regard. It is hoped that this study will also be a part in this line of contribution and serve the purpose at which it is aimed.